A method for preparing a solid-state battery target
By using a combination of sodium molybdate, ammonium molybdate and molybdenum trioxide in copper indium gallium selenide thin-film solar cells, combined with sintering aids and specific process parameters, the problem of uneven distribution of Na ions is solved and the efficiency of solar cells is improved and target density, more efficient battery performance is achieved.
Patent Information
- Application Number
- CN202411304571.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-19
AI Technical Summary
During the preparation of copper indium gallium selenide thin-film solar cells, the high melting point of metal molybdenum leads to uneven distribution of Na ions, affecting the density of the target material and battery efficiency.
Sodium molybdate, ammonium molybdate and molybdenum trioxide are used as raw materials, and through a specific molar ratio and sintering aid combination, vacuum ball milling and sintering process, the heating rate and temperature are controlled to ensure the uniform introduction of sodium ions and grain boundary movement. Improve the density of the target material.
The efficiency of solar cells is significantly improved, ensuring the uniform distribution of sodium ions and the density of the target material, and thus improving the overall performance of the battery.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The present application relates to the field of solid-state batteries, and more specifically, to a method for preparing a solid-state battery target material. Background Art
[0002] In the context of global energy shortage, solar energy has become the most promising green and clean energy. Among various solar cells, copper indium gallium selenide (CIGS) thin-film solar cells have the characteristics of high stability, high light absorption coefficient, strong radiation resistance and long service life.
[0003] Among the various preparation methods of copper indium gallium selenide (CIGS) thin film solar cells, sputtering is currently the most cutting-edge technology for producing the absorption layer of copper indium gallium selenide thin film. Studies have shown that doping alkali metals such as Li, Na, and K into the CIGS thin film structure can significantly improve the conversion efficiency of CIGS solar thin film cells, among which Na has the most obvious improvement effect.
[0004] The Chinese patent with patent number CN 103160791 B discloses a method for preparing a sodium-doped molybdenum planar sputtering target, comprising the following steps: (1) reacting molybdenum trioxide and sodium hydroxide in water to generate a sodium molybdate aqueous solution, heating the sodium molybdate aqueous solution to 100-120° C. to evaporate the sodium molybdate aqueous solution to obtain anhydrous sodium molybdate; the purity of the molybdenum trioxide is above 99.99%, and the molar ratio of molybdenum trioxide to sodium hydroxide is 1:(1-3); the reaction temperature is 50-70° C.; (2) mixing anhydrous sodium molybdate and molybdenum powder and then ball milling them in a ball mill under argon protection to obtain a mixed powder; the total mass of the anhydrous sodium molybdate and the molybdenum powder and the total mass of the balls added in the ball mill are in a ratio of 1:(10-100); (3) placing the mixed powder in a graphite mold and press-molding it in a cold press to obtain a molding material; the pressure of the cold press is 50-350 kgf / cm 2 (4) placing the molding material in a graphite mold and pressing it in a hot press under nitrogen protection to obtain a sodium-doped molybdenum planar sputtering target; the hot press pressure is 50-150kgf / cm 2 The temperature of the hot press is increased from room temperature to 1000-1100°C, the temperature increase rate is 10-25°C / min, the heating is stopped after 0.3-0.5h of constant temperature, and the product is naturally cooled to room temperature.
[0005] However, on the one hand, the melting point of metallic molybdenum is relatively high. If metallic Mo is used as a carrier to introduce a Na ion source, a high-temperature environment is required during the processing, which can easily cause uneven Na distribution and affect the density of the target material. If the density of the target material is low, it will affect the battery efficiency. Summary of the invention
[0006] The present application provides a method for preparing a solid-state battery target material, which can uniformly introduce sodium into a carrier. The obtained target material has good density and can greatly improve the battery efficiency.
[0007] The present application provides a method for preparing a solid-state battery target material, which adopts the following technical solution:
[0008] A method for preparing a solid-state battery target material comprises the following steps:
[0009] (1) Weighing sodium molybdate, ammonium molybdate, and molybdenum trioxide in a molar ratio of (0.12-0.15):(0.2-0.3):1, adding a sintering aid, and ball milling to obtain a prefabricated powder;
[0010] (2) Sintering the prefabricated powder in a vacuum environment at a sintering temperature of 590-610°C; during the heating process, the temperature is increased to 240-260°C at a heating rate of 20-35°C / min, then increased to 400-420°C at a heating rate of 50-65°C / min, and finally increased to 590-610°C at a heating rate of 30-35°C / min.
[0011] Furthermore, a method for preparing a solid-state battery target material comprises the following steps:
[0012] (1) Weighing sodium molybdate, ammonium molybdate and molybdenum trioxide in a molar ratio of 0.14:0.3:1, adding a sintering aid, and ball milling to obtain a prefabricated powder;
[0013] (2) The prefabricated powder is sintered in a vacuum environment at a sintering temperature of 600°C. During the heating process, the temperature is increased to 250°C at a heating rate of 30°C / min, then to 410°C at a heating rate of 55°C / min, and finally to 600°C at a heating rate of 30°C / min.
[0014] Furthermore, the sintering aid is aluminum powder, and the molar ratio of aluminum powder to sodium molybdate is (0.3~0.5):1.
[0015] Furthermore, the particle sizes of the sodium molybdate, molybdenum trioxide and ammonium molybdate are all 90-100 μm, and the particle size of the sintering aid is 120`-150 μm.
[0016] Furthermore, during the ball milling process, the dispersion medium is anhydrous ethanol, the ratio of the total mass of the powder to the total mass of the balls added in the ball mill is 1:(80-90), the rotation speed of the ball mill is 400-500rpm, and the ball milling time is 120-140min.
[0017] Furthermore, in the step (2), the prefabricated powder is kept at a temperature of 590-610° C. for 0.6-1.2 h and a pressure of 35-40 MPa.
[0018] Furthermore, in the step (2), the prefabricated powder is kept at 600° C. for 0.8 h and at a pressure of 40 MPa.
[0019] In summary, this application has the following beneficial effects:
[0020] In the preparation method of the present application, sodium molybdate and molybdenum oxide are mainly used as sodium source and molybdenum source. The two have similar melting points, which are more conducive to the introduction of sodium molybdate. However, the degree of improvement in battery efficiency is still limited. After a lot of research, ammonium molybdate is added to the raw material system, and the component dosage of the raw material system is determined. Further, the parameters of the sintering process are determined; not only is it conducive to the introduction of sodium ions, but also during the sintering process, the transformation of molybdenum trioxide, molybdenum dioxide, and molybdenum is more reasonable, which improves the grain boundary movement and grain growth of the sintering process, improves the density of the target material and other properties, and is conducive to improving battery efficiency. DETAILED DESCRIPTION
[0021] The present application is further described in detail below with reference to the embodiments.
[0022] Example
[0023] The present application discloses a method for preparing a solid-state battery target material, comprising the following steps:
[0024] (1) Sodium molybdate, ammonium molybdate and molybdenum trioxide are weighed in a molar ratio of (0.12-0.15): (0.2-0.3): 1, and a sintering aid is added. The sintering aid is aluminum powder, and the molar ratio of aluminum powder to sodium molybdate is (0.3-0.5): 1. After ball milling, a preformed powder is obtained; the particle size of sodium molybdate, molybdenum trioxide and ammonium molybdate is 90-100 μm, and the particle size of the sintering aid is 120`~150 μm. During the ball milling process, the dispersion medium is anhydrous ethanol, the ratio of the total mass of the powder to the total mass of the balls added in the ball mill is 1: (80-90), the speed of the ball mill is 400-500 rpm, and the ball milling time is 120-140 min.
[0025] (2) Sintering the prefabricated powder in a vacuum environment at a sintering temperature of 590-610°C. The prefabricated powder is kept at 590-610°C for 0.6-1.2 h at a pressure of 35-40 MPa. In the specific heating process, the temperature is increased to 240-260°C at a heating rate of 20-35°C / min, then increased to 400-420°C at a heating rate of 50-65°C / min, and finally increased to 590-610°C at a heating rate of 30-35°C / min.
[0026] The following is an explanation through specific embodiments.
[0027] Example 1
[0028] Embodiment 1 discloses a method for preparing a solid-state battery target material, comprising the following steps:
[0029] (1) Sodium molybdate, ammonium molybdate and molybdenum trioxide were weighed in a molar ratio of 0.14:0.3:1, and aluminum powder was added. The pre-made powder was obtained after ball milling. The molar ratio of aluminum powder to sodium molybdate was 0.4:1. During the ball milling process, the dispersion medium was anhydrous ethanol, the ratio of the total mass of the powder to the total mass of the balls added in the ball mill was 1:85, the speed of the ball mill was 500 rpm, and the ball milling time was 130 min.
[0030] (2) The prefabricated powder was sintered in a vacuum environment at a sintering temperature of 600 °C. During the heating process, the temperature was increased to 250 °C at a heating rate of 30 °C / min, then to 410 °C at a heating rate of 55 °C / min, and finally to 600 °C at a heating rate of 30 °C / min. The prefabricated powder was kept at 600 °C for 0.8 h under a pressure of 40 MPa.
[0031] Embodiment 2-6
[0032] The difference between Examples 2-6 and Example 1 is that the parameters of the preparation process are different, as shown in Table 1.
[0033] Table 1 Process parameters of Examples 1-6
[0034] ,
[0035]
[0036] Comparative Example
[0037] The difference between Comparative Example 1 and Example 1 is that ammonium molybdate is not added.
[0038] The difference between Comparative Example 2 and Example 1 is that the molar ratio of sodium molybdate, ammonium molybdate and molybdenum trioxide is 0.14:0.1:1.
[0039] The difference between Comparative Example 3 and Example 1 is that the molar ratio of sodium molybdate, ammonium molybdate and molybdenum trioxide is 0.14:0.4:1.
[0040] The difference between Comparative Example 4 and Example 1 is that the molar ratio of sodium molybdate, ammonium molybdate and molybdenum trioxide is 0.11:0.3:1.
[0041] The difference between Comparative Example 5 and Example 1 is that the molar ratio of sodium molybdate, ammonium molybdate and molybdenum trioxide is 0.16:0.3:1.
[0042] The difference between Comparative Example 6 and Example 1 is that the sintering temperature is 600°C; during the heating process, the temperature is increased to 250°C at a heating rate of 15°C / min, then increased to 140°C at a heating rate of 45°C / min, and finally increased to 600°C at a heating rate of 25°C / min.
[0043] The difference between Comparative Example 7 and Example 1 is that the sintering temperature is 600°C; during the heating process, the temperature is increased to 250°C at a heating rate of 40°C / min, then increased to 140°C at a heating rate of 70°C / min, and finally increased to 600°C at a heating rate of 40°C / min.
[0044] The difference between Comparative Example 8 and Example 1 is that the sintering temperature is 600°C; during the heating process, the temperature is increased to 230°C at a heating rate of 25°C / min, then increased to 390°C at a heating rate of 55°C / min, and finally increased to 600°C at a heating rate of 35°C / min.
[0045] The difference between Comparative Example 9 and Example 1 is that the sintering temperature is 600°C; during the heating process, the temperature is increased to 270°C at a heating rate of 25°C / min, then increased to 430°C at a heating rate of 55°C / min, and finally increased to 600°C at a heating rate of 35°C / min.
[0046] The difference between Comparative Example 10 and Example 1 is that the sintering temperature is 620°C; during the heating process, the temperature is increased to 250°C at a heating rate of 30°C / min, then increased to 410°C at a heating rate of 55°C / min, and finally increased to 620°C at a heating rate of 30°C / min.
[0047] The difference between Comparative Example 11 and Example 1 is that the sintering temperature is 580°C; during the heating process, the temperature is increased to 250°C at a heating rate of 30°C / min, then increased to 410°C at a heating rate of 55°C / min, and finally increased to 580°C at a heating rate of 30°C / min.
[0048] The difference between Comparative Example 12 and Example 1 is that the sintering temperature is 600° C.; during the heating process, the temperature is increased to 600° C. at a heating rate of 40° C. / min.
[0049] The difference between Comparative Example 13 and Example 1 is that molybdenum oxide is replaced by an equal amount of metallic molybdenum.
[0050] Performance Testing
[0051] After the target material in this embodiment or comparative example is prepared and sintered, it is prepared into a composite ceramic target material with a diameter of 100 mm and a thickness of 10 mm, and is used for the preparation of a copper indium gallium selenide solar cell. The specific preparation is as follows:
[0052] The molybdenum layer was plated on the PI substrate by sputtering, and the evaporation condition was that the initial vacuum degree was 1×10 -3 Pa, heated to a vacuum degree of 5.0×10 -4 Pa, argon gas flow rate of 60 ml / min, sputtering power of 200 W, sputtering time of 60 minutes; and then a copper indium gallium selenide absorption layer is plated.
[0053] The efficiency of the prepared cell was tested. The current-voltage data of the solar cell was measured on an Oriel solar simulator and a Keithley 2400 current source instrument. The efficiency of the solar cell can be directly obtained from the Labview I-V running software. Calculate the cell efficiency improvement rate = (cell efficiency prepared by the target material of the embodiment or comparative example - efficiency of the copper indium gallium selenide solar cell without molybdenum coating prepared under the same conditions) / efficiency of the copper indium gallium selenide solar cell without molybdenum coating prepared under the same conditions. In this application, the efficiency of the copper indium gallium selenide solar cell without molybdenum coating prepared under the same conditions is 12.1%. The results are shown in Table 2.
[0054] Table 2 Battery efficiency improvement rate of target materials prepared in the examples and comparative examples
[0055]
[0056]
[0057] According to the test results of Examples 1-6 and Comparative Example 13, the target material prepared by the preparation method of the present application can well improve the battery efficiency. Further observation, from the test results of Example 1, Examples 4-6 and Comparative Example 4-5, it can be seen that the amount of sodium molybdate used has a certain effect on the performance of the target material, but as the amount of sodium molybdate increases, the rate of improvement in the initial stage of battery efficiency becomes higher and higher, but as the amount of sodium molybdate further increases, the rate of improvement in battery efficiency decreases. This is because in the process of target material preparation, the remaining raw materials and process parameters will react with sodium molybdate, thereby affecting the overall performance of the target material. According to this conclusion, further observation of the performance of Comparative Example 1 shows that without adding ammonium molybdate, the rate of improvement in the final battery efficiency decreases more, indicating that the use of ammonium molybdate does have a positive effect on the performance of the target material. It can be further seen that the use of ammonium molybdate is conducive to the introduction of sodium ions, improving the density of the target material, and thus better improving the rate of improvement in battery efficiency.
[0058] Further analysis of the performance of Comparative Examples 2 and 3 revealed that if the amount of ammonium molybdate used is too little, the role of ammonium molybdate cannot be fully exerted. However, if the amount of ammonium molybdate used is too much, it may affect the material transformation and crystal phase transformation in the sintering process, which in turn leads to poor performance of the final target material and affects the improvement of battery efficiency.
[0059] In addition to the influence of raw materials on the performance of the target material, it was found during the research process that the parameter control of the sintering process will also have a great influence on the performance of the target material. Among them, Comparative Example 12 reflects that the application increases the temperature in stages, which has a positive effect on the performance of the target material. Further, from the analysis of the performance of Comparative Examples 6-9, it can be seen that the heating rate of the heating process and the staged target temperature have a great influence on the performance of the target material. This is because the heating process of the present application is more conducive to the interaction between the components of the raw materials, so that the material and the crystal phase are transformed in a favorable way, which is conducive to the introduction of sodium ions, improves the density of the target material, and thus has a better battery efficiency improvement rate. In addition, from the analysis of the test results of Comparative Examples 10 and 11, it can be seen that for the raw material system of the present application, the sintering temperature is 590-610°C, which makes the target material have good performance.
[0060] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a solid-state battery target, characterized in that: The following steps are involved: (1) Weighing sodium molybdate, ammonium molybdate and molybdenum trioxide in a molar ratio of (0.12-0.15):(0.2-0.3):1, adding a sintering aid, and ball milling to obtain a prefabricated powder; the sintering aid is aluminum powder, and the molar ratio of aluminum powder to sodium molybdate is (0.3-0.5):1; (2) The prefabricated powder is sintered in a vacuum environment at a sintering temperature of 590-610°C. During the heating process, the temperature is increased to 240-260°C at a heating rate of 20-35°C / min, then to 400-420°C at a heating rate of 50-65°C / min, and finally to 590-610°C at a heating rate of 30-35°C / min. The holding time at 590-610°C is 0.6-1.2h and the pressure is 35-40 MPa.
2. The method for preparing a solid-state battery target according to claim 1, characterized in that: (1) Weighing sodium molybdate, ammonium molybdate and molybdenum trioxide in a molar ratio of 0.14:0.3:1, adding a sintering aid, and ball milling to obtain a prefabricated powder; (2) The prefabricated powder is sintered in a vacuum environment at a sintering temperature of 600°C. During the heating process, the temperature is increased to 250°C at a heating rate of 30°C / min, then to 410°C at a heating rate of 55°C / min, and finally to 600°C at a heating rate of 30°C / min.
3. The method for preparing a solid-state battery target according to claim 1, characterized in that: The particle sizes of the sodium molybdate, molybdenum trioxide and ammonium molybdate are all 90-100 μm, and the particle size of the sintering aid is 120-150 μm.
4. The method for preparing a solid-state battery target material according to claim 3, characterized in that: During the ball milling process, the dispersion medium is anhydrous ethanol, the ratio of the total mass of the powder to the total mass of the balls added in the ball mill is 1:(80-90), the rotation speed of the ball mill is 400-500rpm, and the ball milling time is 120-140min.
5. The method for preparing a solid-state battery target material according to claim 1, characterized in that: In the step (2), the holding time at 600° C. is 0.8 h and the pressure is 40 MPa.
Citation Information
Patent Citations
Preparation method of sodium-doped molybdenum plane sputtering target material
CN103160791B
Method for preparing sodium-doped molybdenum sputtering target material
CN104073771A
Preparation method of doped molybdenum target material
CN106591786A
Preparation method of sodium-containing molybdenum oxide ceramic sputtering target material
CN115196964A
Low-temperature rapid sintering preparation method of sodium molybdenum ceramic target material
CN118324524A
